2013
DOI: 10.1051/0004-6361/201220646
|View full text |Cite
|
Sign up to set email alerts
|

Crantor, a short-lived horseshoe companion to Uranus

Abstract: Context. Stable co-orbital motion with Uranus is vulnerable to planetary migration, but temporary co-orbitals may exist today. So far, only two candidates have been suggested, both moving on horseshoe orbits: 83982 Crantor (2002 GO 9 ) and 2000 SN 331 . Aims. (83982) Crantor is currently classified in the group of the Centaurs by the MPC although the value of its orbital period is close to that of Uranus. Here we revisit the topic of the possible 1:1 commensurability of (83982) Crantor with Uranus, explore its… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Uranus has one known temporary (∼ 20 kyr) horseshoe companion (34) and 2011 QF 99 , the temporary L4 Trojan reported here. The Uranian co-orbital region is thought to be mostly unstable (6) although some stable niches may exist (7).…”
Section: Yn 107mentioning
confidence: 52%
“…Uranus has one known temporary (∼ 20 kyr) horseshoe companion (34) and 2011 QF 99 , the temporary L4 Trojan reported here. The Uranian co-orbital region is thought to be mostly unstable (6) although some stable niches may exist (7).…”
Section: Yn 107mentioning
confidence: 52%
“…The identified resonant configurations are temporary as the minor planets experience close encounters with the giant planets. This is akin to the temporary capture of NEAs in the (prograde) 1/1 resonance (Namouni et al 1999;Christou 2000) with the terrestrial planets and that of Centaurs in the same resonance with Uranus and Neptune(de la Fuente Marcos & de la Fuente Marcos 2012Marcos , 2013Alexandersen et al 2013).…”
Section: Numerical Integrations Of Objects In Retrograde Orbitsmentioning
confidence: 99%
“…In addition, 2014 YX 49 is identified as the second UT, temporarily on a high-inclined (i = 25.5 • ) tadpole orbit around L 4 (de la Fuente Marcos & de la Fuente Marcos 2017). Moreover, it was reported that there exist several possible Uranus companions such as 83982 (Crantor), 2002VG 131 , 2010EU 65 and 2015 , which are supposed to be on the transient horseshoe, quasi-satellite or even recurring co-orbital orbits (Gallardo 2006;de la Fuente Marcos & de la Fuente Marcos 2013, 2015. A detailed analysis of the dynamical evolution of these objects show that ephemeral multi-body MMRs could trigger the capture, ejection and switching between resonant co-orbital states of transient Uranus companions.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed analysis of the dynamical evolution of these objects show that ephemeral multi-body MMRs could trigger the capture, ejection and switching between resonant co-orbital states of transient Uranus companions. Meanwhile, Jupiter and Neptune are found to render the long-term stability of them (de la Fuente Marcos & de la Fuente Marcos 2013Marcos , 2014Marcos , 2015Marcos , 2017. Actually, the specific mechanisms behind these objects are different from each other, indicating complicated dynamical properties of Uranus co-orbital regions.…”
Section: Introductionmentioning
confidence: 99%